Upper bound of second Hankel determinant for subclass of close-to-convex functions / Muhammad Fazrul Azmi... [et al.] - Azmi, Muhammad Fazrul; Muhd Jelaini, Amin Iman; Jafari, Aniza Izati (2019)
Geometric function theory is an extraordinary area of complex analysis. This area of study is more often associated with geometric properties of analytic function such as extremal properties, radius properties, representation theorem and coefficient bound. Many researchers raised the interest in studying properties in different classes that have been introduced. In this research, we focus on defining new subclasses of analytic functions, L(a,<5,t,s) afterwards determining the upper bound of second Hankel determinant for the selected class of function.